Jerome - Hnizdovsky, Jacques ([S. l.] : [s. n.], 1978)
Prikaz mačka.
Signatura autora ispod otiska olovkom: Hnizdovsky: Jerome 1978 11/150.
Digitalna reprodukcija
Hnizdovsky : Woodcuts, 1944-1975. Gretna : Pelican Publishing Company, 1976.
Keywords: Drvorezi